2017
DOI: 10.1093/pm/pnx036
|View full text |Cite
|
Sign up to set email alerts
|

Primary Motor Cortex Organization Is Altered in Persistent Patellofemoral Pain

Abstract: These findings provide evidence of altered M1 organization in individuals with PFP compared with healthy controls. Notably, no difference in M1 organization was observed for the medial and lateral heads of the quadriceps in PFP. These data have relevance for our understanding of the pathophysiology of PFP and for the design of future treatments that aim to target M1 in this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 57 publications
2
54
0
Order By: Relevance
“…Numerous studies have suggested a link between altered corticomotor excitability and the symptoms of chronic musculoskeletal pain (Schabrun, Elgueta-Cancino, & Hodges, 2017;Tsao, Galea, & Hodges, 2008;Te, Baptista, Chipchase, & Schabrun, 2017;Tsao, Danneels, & Hodges, 2011;Schabrun, Hodges, Vicenzino, Jones, & Chipchase, 2015). However, only one study has conducted a longitudinal investigation of this mechanism in response to pain.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have suggested a link between altered corticomotor excitability and the symptoms of chronic musculoskeletal pain (Schabrun, Elgueta-Cancino, & Hodges, 2017;Tsao, Galea, & Hodges, 2008;Te, Baptista, Chipchase, & Schabrun, 2017;Tsao, Danneels, & Hodges, 2011;Schabrun, Hodges, Vicenzino, Jones, & Chipchase, 2015). However, only one study has conducted a longitudinal investigation of this mechanism in response to pain.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in map representations in musculoskeletal pain syndromes are frequently reported (Coppieters et al, 2016). M1 map differences include map size, location, and/or number of peaks, volume, and the overlap between maps for different muscles (Massé-Alarie et al, 2017;Schabrun et al, 2014;Te, Baptista, Chipchase, & Schabrun, 2017;Tsao et al, 2011b;Ziemann & Siebner, 2008). Although the importance of changes in M1 organisation is not yet fully understood, previous research has found associations between differences of some parameters are concurrent with alterations in motor control, such as delayed muscle activations .…”
Section: Motor Cortex Organisation Differs Between Individuals Withmentioning
confidence: 99%
“…In back pain, the representation of superficial lumbar longissimus is more posterior such that it approximates the same location as the deep multifidus muscle (Schabrun et al, 2015;Tsao et al, 2011b). In patellofemoral pain, representations of rectus femoris, vastus lateralis, and vastus medialis are shifted anteriorly with greater overlap (Te et al, 2017). In back pain, greater overlap of M1 representations has been linked with less ability to separately move spine regions (Elgueta-Cancino et al, 2018;Tsao et al, 2011b).…”
Section: Differences In Location Of M1 Representations In Other Body mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the primary motor cortex representation of the back muscles is shifted posteriorly and displays greater overlap in chronic low back pain using transcranial magnetic stimulation (TMS) [49,50,54,55]. Similar sensorimotor cortical adaptations have also been reported in chronic lateral epicondylalgia [4,44], rotator cuff tears [3], anterior cruciate ligament instability [17] and patello-femoral pain syndrome [32,52] indicating altered corticospinal drive to muscles associated with the painful/damaged structure. Short-term experimental muscle pain models in healthy individuals have been used to study the effect of acute nociception on sensory [37,38,45] and motor cortical excitability [34,51].…”
Section: A N U S C R I P T Introductionmentioning
confidence: 87%